Methylation Profile of HOXA 11 Gene in Eutopic Endometrium on Endometriosis Patient with Infertility - Muharam Natadisastra; Valencia Yuwono; Ririn Febri; Asmarinah Asmarinah (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To investigate the HOXA11 gene profile on endometriosis patients with infertility in Indonesia. Methods: This cross sectional study was conducted in Dr. Cipto Mangunkusumo Hospital from July 2015- June 2016. The subjects were endometriosis patients with infertility who have been confirmed histopathological. The control group was taken from non-endometriosis and fertile patients. Eutopic endometrium samples were taken and examined for the methylation of HOXA 11 gene. Results: Both groups consist of six patients. The difference of methylation of HOXA 11 gene between those two groups is statistically significant (p=0.03). There was hyper methylation in endometriosis group. Conclusion: There is a hyper methylation of HOXA 11 gene in eutopic endometrium of endometriosis patients with infertility. Thus, possibly can explain the poor endometrial receptivity in endometriosis patient and give a broad research area in epigenetic therapy of endometriosis. [Indones J Obstet Gynecol 2018; 6-2: 110-113] Keywords: endometriosis, epigenetic, HOXA 11, infertility, methylation